2021
DOI: 10.1093/hmg/ddab222
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal migration behavior linked to Rac1 signaling contributes to primordial germ cell exhaustion in Fanconi anemia pathway-deficient Fancg−/− embryos

Abstract: Fanconi anemia (FA) is a rare human genetic disorder characterized by bone marrow failure, predisposition to cancer and developmental defects including hypogonadism. Reproductive defects leading to germ cell aplasia are the most consistent phenotypes seen in FA mouse models. We examined the role of the nuclear FA core complex gene Fancg in the development of primordial germ cells (PGCs), the embryonic precursors of adult gametes, during fetal development. PGC maintenance was severely impaired in Fancg−/− embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…As we observe expected Fancg -KO numbers at E14.5 but not at weaning (E21), Domenech et al argue that although the compensatory mechanisms reduce the differences between FANCG-deficient and WT embryos by E14.5, early HSC defects in Fancg −/− embryos (E11.5-E12.5) ultimately result in perinatal lethality [ 37 ]. Nevertheless, consistent with other FA mouse models in previous studies, our KO mice were also infertile with gross germ cell defects and reduced size of testes/ovaries, which might be due to the RAC1-based exhaustion of primordial germ cells in the absence of FANCG [ 46 ]. Otherwise, Fancg -KO developed normally without any overt macroscopic abnormalities.…”
Section: Discussionsupporting
confidence: 89%
“…As we observe expected Fancg -KO numbers at E14.5 but not at weaning (E21), Domenech et al argue that although the compensatory mechanisms reduce the differences between FANCG-deficient and WT embryos by E14.5, early HSC defects in Fancg −/− embryos (E11.5-E12.5) ultimately result in perinatal lethality [ 37 ]. Nevertheless, consistent with other FA mouse models in previous studies, our KO mice were also infertile with gross germ cell defects and reduced size of testes/ovaries, which might be due to the RAC1-based exhaustion of primordial germ cells in the absence of FANCG [ 46 ]. Otherwise, Fancg -KO developed normally without any overt macroscopic abnormalities.…”
Section: Discussionsupporting
confidence: 89%
“…FANC family of genes and related DNA interstrand crosslink pathway are identified for Fanconi anemia pathology, 283 and FANCG is responsible for the PGC migration. 245 Overexpression of hPGC marker gene PRDM14 is detected in lymphoblastic lymphomas, 284 suggesting PRDM14 as a proto-oncogene involved in lymphoblastic lymphoma formation. It has been suggested that depletion of PRDM14 expression may be an effective and radical therapy for solid cancers.…”
Section: Precursors For the Gametes: Human Primordial Germ Cellsmentioning
confidence: 99%
“…235 Screening for the factors involved in PGC migration has identified a number of signaling molecules essential for the migration from a variety of animals, including Drosophila, 138,236 Xenopus laevis, 237 zebrafish, 119,[238][239][240] chicken, 119,241 and mice. 15,227,230,[242][243][244][245][246][247][248][249][250][251] Several signaling pathways of PGC migration are conserved in humans. Main signaling molecules and their pathways involved in PGC migration include SDF1-CXCR4, KIT-KITLG, HMGCR, and cholesterol.…”
Section: Migration and Colonization Of Hpgcsmentioning
confidence: 99%
“…Neurodegenerative disorders such as Alzheimer’s disease and Parkinson’s disease are both related to aberrant Rac1-associated signal pathways [ 50 , 51 ]. Abnormally elevated Rac1 activity could alter the cell migration patterns to affect body development [ 80 , 81 ]. Thus, maintaining proper Rac1 activity is a key basis for normal development and homeostasis.…”
Section: Rac1 Regulates Cell Migration and Tumor Invasion And Metastasismentioning
confidence: 99%